Modes of Address in the First Edition of Thomas Hardy’s “Poems of 1912-13” - Muhammad Dirgantara Esa Valentino Am; Muhammad Agus Hardiansyah (Journal of English Language Studies, 2022)
The use of place and of time as organizing forms in “Poems of 1912-13”, first appeared in Satires and Circumstances (1914), have been discussed by other readers. The modes of address and their expressive significances as one of the sequence’s expressive vehicles, however, have not been. It is important to discuss the modes of address as it deepens the readers’ understanding of the elegiac sequence whose status occupies a prominent place in the poet’s oeuvre. In discussing the modes of address in “Poems of 1912-13,” the descriptive-interpretive close reading method was used. Although the paper’s focus is on the modes of address, other textual features were also analyzed where relevant.   Five modes of address--i.e. the second-person, the third-person, the ‘ventriloquizing’, the ‘composite’, and the ‘unique’--are identified and described. These modes of address, furthermore, are proposed to signify and dramatize Hardy’s hauntedness in the beginning, the ways he comes to terms with that state in the middle, and the peace he arrives at in the end. The second-person mode signifies Hardy’s hauntedness. The third-person mode signifies and dramatizes his first strategy to solve the problem. The ‘ventriloquizing’ mode signifies and dramatizes his second strategy. The ‘composite’ mode signifies and dramatizes his third and final strategy. Finally, the ‘unique’ mode signifies and dramatizes his peaceful state in the end. The paper is concluded by raising the issue of the poet’s later addition to the sequence’s first version and by pointing out further aspects of the sequence to be explored.